Emerging business models in local energy markets - Schwidtal, Jan Marc (2023)
Schwidtal, J. M., Piccini, P., Troncia, M., Chitchyan, R., Montakhabi, M., Francis, C., Gorbatcheva, A., Capper, T., Mustafa, M. A., Andoni, M., Robu, V., Bahloul, M., Scott, I. J., Mbavarira, T., España, J. M. E., & Kiesling, L. (2023). Emerging business models in local energy markets: a systematic review of peer-to-peer, community self-consumption, and transactive energy models. Renewable and Sustainable Energy Reviews, 179(June), 1-48. [113273]. https://doi.org/10.1016/j.rser.2023.113273 -- This publication is part of the work of the Global Observatory on Peer-to-Peer, Community Self-Consumption and Transactive Energy Models (GO-P2P), a task of the User-Centred Energy Systems Technology Collaboration Programme (Users TCP), under the auspices of the International Energy Agency. GO-P2P benefits from the support of Australia, Belgium, Ireland, Italy, the Netherlands, Switzerland, the United Kingdom and United States. GO-P2P is also supported by the EPSRC EnergyREV project EnergyREV (EP/S031863/1).